Nutrient digestion and utilization in farm animals [ modelling approaches - Kebreab, E. (CABI, 2006)
Brings together the papers presented at the Sixth International Workshop on Modelling Nutrient Utilization in Farm Animals. Divided into six sections, th purpose of this book is to present research in modelling nutrient digestion and utilization in cattle, sheep, pigs, poultry and fish. It will interest researchers and students of animal science.